Pedagogy, or martial arts - the rivalry in quality, examples of Kazimierz Wielki University publications - Pujszo, Małgorzata; Stępniak, Robert; Wilczyńska, Sylwia (Journal of Education, Health and Sport, 2017)
Objective: To compare the basic bibliometric parameters of publications in journals in various fields of study as an indicator of rivalry. Material and methods: There were 24 publications on combat sports and 24 publications on pedagogy of labor and andragogy between 2015 and 2016. Results: It demonstreted a significant qualitative and quantitative differences in publication quality. Conclusions: The result of the study of the scientific rivalry should be a source of discussion on ways and possibilities of improving the quality of emitted publications of scientists of Kazimierz Wielki University.